The MeCP2E1/E2-BDNF-miR132 Homeostasis Regulatory Network Is Region-Dependent in the Human Brain and Is Impaired in Rett Syndrome Patients - Pejhan, Shervin; Del Bigio, Marc R.; Rastegar, Mojgan (Frontiers in Cell and Developmental Biology, 2020)
Rett Syndrome (RTT) is a rare and progressive neurodevelopmental disorder that is caused by de novo mutations in the X-linked Methyl CpG binding protein 2 (MECP2) gene and is subjected to X-chromosome inactivation. RTT is commonly associated with neurological regression, autistic features, motor control impairment, seizures, loss of speech and purposeful hand movements, mainly affecting females. Different animal and cellular model systems have tremendously contributed to our current knowledge about MeCP2 and RTT. However, the majority of these findings remain unexamined in the brain of RTT patients. Based on previous studies in rodent brains, the highly conserved neuronal microRNA “miR132” was suggested to be an inhibitor of MeCP2 expression. The neuronal miR132 itself is induced by Brain Derived Neurotrophic Factor (BDNF), a neurotransmitter modulator, which in turn is controlled by MeCP2. This makes the basis of the MECP2-BDNF-miR132 feedback regulatory loop in the brain. Here, we studied the components of this feedback regulatory network in humans, and its possible impairment in the brain of RTT patients. In this regard, we evaluated the transcript and protein levels of MECP2/MeCP2E1 and E2 isoforms, BDNF/BDNF, and miR132 (both 3p and 5p strands) by real time RT-PCR, Western blot, and ELISA in four different regions of the human RTT brains and their age-, post-mortem delay-, and sex-matched controls. The transcript level of the studied elements was significantly compromised in RTT patients, even though the change was not identical in different parts of the brain. Our data indicates that MeCP2E1/E2-BDNF protein levels did not follow their corresponding transcript trends. Correlational studies suggested that the MECP2E1/E2-BDNF-miR132 homeostasis regulation might not be similarly controlled in different parts of the human brain. Despite challenges in evaluating autopsy samples in rare diseases, our findings would help to shed some light on RTT pathobiology, and obscurities caused by limited studies on MeCP2 regulation in the human brain.